Employer Branding, Person-Job Fit, and Psychological Empowerment's Impact on Turnover Intention of Gen Y and Z in Indonesian Private Banks - Badiah, Badiah; Rojuaniah, Rojuaniah (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2025)
The objective of the study is to examine the impact of employer branding, person-job fit, and psychological empowerment on turnover intention among Generation Y and Z employees in private banks in Indonesia. This study focuses on analyzing indicators for each variable to describe the characteristics of Generation Y and Generation Z employees. The findings will aid in formulating effective management strategies to reduce turnover intention. This quantitative study employs the Structural Equation Model (SEM) with data collected through online questionnaires from 243 respondents in JABODETABEK areas from May 11 to May 23, 2024. Purposive sampling criteria included Generation Y and Z employees with at least one year of work experience in a private bank and a minimum diploma education. The findings reveal that employer branding, especially regarding compensation and benefits, significantly affects turnover intention, aligning with prior research. Both person-job fit and psychological empowerment negatively impact turnover intention, emphasizing the importance of role alignment and workplace empowerment in reducing employee departures. Generational differences between Generations Y and Z do not significantly moderate these relationships. This research aids organizations in developing effective retention strategies to retain top talent and enhance performance.